2010
DOI: 10.1007/s12055-010-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of foreign body superior mediastinum: a case report

Abstract: Foreign body in the superior mediastinum following a fall on a box is uncommon. We present a 27 years old woman with history of fall on a box containing embroidery needles 3 years ago. Chest Xray and fluoroscopy revealed two needles; one at the left parasternal subcutaneous plane was removed and advised removal of the second needle at the superior mediastinum. She defaulted and came after a recent trivial chest injury. After confirmation, by thoracotomy, a rusted needle (of 1 in. size) embedded between the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3]5,7] Common examinations used to confirm the final diagnosis are chest X-rays, chest CTs, bronchoscopies, and esophagoscopies. [1][2][3][4][5][6][7][8] In cases involving foreign mediastinal bodies, one of the most frequent complications is migration. Sivaraman et al [8] reported the case of a 27-year-old woman who was diagnosed with a needle in the superior mediastinum that was caused by falling on a box of needles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3]5,7] Common examinations used to confirm the final diagnosis are chest X-rays, chest CTs, bronchoscopies, and esophagoscopies. [1][2][3][4][5][6][7][8] In cases involving foreign mediastinal bodies, one of the most frequent complications is migration. Sivaraman et al [8] reported the case of a 27-year-old woman who was diagnosed with a needle in the superior mediastinum that was caused by falling on a box of needles.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In cases involving foreign mediastinal bodies, one of the most frequent complications is migration. Sivaraman et al [8] reported the case of a 27-year-old woman who was diagnosed with a needle in the superior mediastinum that was caused by falling on a box of needles. She did not agree to have surgery because of a lack of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations